Influence of insertion angle and depth on the stresses produced in implants and prosthetic components - a finite element analysis - Fabiano Rito Macedo; Joelson Rodrigues Brum; Millena Barroso Oliveira; Douglas Teixeira da Silva; Walbert de Andrade Vieira; Igor Felipe Pereira Lima; Luiz Renato Paranhos; Rui Barbosa de Brito Junior (Acta Scientiarum. Health Sciences, 2024)
This study assessed the influence of different insertion angles and depths on the stress distribution in implants and prosthetic components subjected to axial and oblique loading. The study followed the Checklist for Reporting In-vitro Studies (CRIS) recommendations. The implant was placed in the region of element 36, according to the following models: M1 (0 mm / 0°); M2 (0 mm / 17°); M3 (0 mm / 30°); M4 (2 mm / 0°); M5 (2 mm / 17°); M6 (2 mm / 30°). All models were subjected to axial and oblique loading with an intensity of 100 N. Stress was assessed according to the Rankine and Von Mises criteria and analyzed qualitatively and quantitatively. There were minimal differences between the implants placed at bone crest height and 2 mm below it. In the external portion of the intermediates, the models angled at 30° presented higher stress concentrations under both loads. The internal part of the intermediates and the crown screw showed higher peaks as the implant angles increased. The models with inclined implants positioned below the bone crest were slightly compromised. As for the other models, the results were far from the yield point of the analyzed materials, indicating a long service life of implants and their prosthetic components in the assessed conditions.